Canopy Management to Improve Grape Yield and Wine Quality - Principles and Practices - Smart, R.E.; Dick, Joy K.; Gravett, Isabella M.; Fisher, B.M. (South African Journal of Enology and Viticulture, 2017)
This paper reviews the subject of canopy management with an attempt to develop principles. These principles provide guidelines for canopy surface area amount; spacing between canopies; within canopy shade, especially for the fruiting/ renewal zone; balance between fruit and shoot growth; and uniformity of location of fruit/renewal zones, shoot tips and cane bases. Field techniques of point quadrat analysis and canopy scoring are introduced as an aid to defining problem canopies. These techniques are cheap, quick and effective. A set of twenty-one numeric indices and descriptors to assess winegrape canopies is then presented as a winegrape canopy ideotype, which can be further used as management guidelines. Recent publications are reviewed from various aspects of canopy management. These include vigour control, shoot trimming, leaf removal in the fruit zone and training system responses. The paper concludes with presentation of the authors’ unpublished data on the effects of canopy microclimate on yield and wine quality. The trial was conducted with the cultivar Cabernet franc on a deep, fertile soil in a cool, high rainfall region. Canopy division using the Ruakura Twin Two Tier doubled yield compared to dense, vertical shoot positioned canopies which are common in New Zealand. Shade caused reduction in all yield components, and also delayed fruit ripening and reduced wine quality. Similar results were obtained by comparing fruit production at different heights with the Te Kauwhata Three Tier trellis system, where lower tiers were shaded at the canopy exterior. The results confirm that grape yield and wine quaiity can be simultaneously increased by improved canopy management of shaded vineyards.